Bilateral Central Retinal Vein Occlusion Associated with Axitinib Therapy: A Case Report. (16th March 2023) - Pyare, Richa; Ganvir, Amol; Goyal, Shina; Rao, Chetan; Dutta Majumder, Parthopratim
ABSTRACT: Purpose: To describe a case of retinal vascular occlusion and cerebrovascular accident following axitinib therapy. Methods: A retrospective chart review. Result: A 65-year-old gentleman with a history of renal cell carcinoma and subsequent metastases to the brain was on axitinib at an oral daily dose of 10 mg. The patient reported a loss in vision in the right, followed by the left eye, and suffered an episode of cerebrovascular accident. Retinal examination revealed right eye optic nerve pallor with sclerosed vessels, possibly sequelae of central retinal vein occlusion, and left eye showed multiple retinal hemorrhages in all quadrants with macular edema, suggestive of central retinal vein occlusion. He was not a known hypertensive, his renal carcinoma was in remission, and his other systemic parameters were within acceptable limits. Conclusions: Axitinib can cause retinal vein occlusions, and clinicians, both oncologists, and ophthalmologists need to be aware of this rare but potentially blinding side effect.